MEMBANGUN JIWA KEWIRAUSAHAAN SISWA SEJAK DINI: PENTINGNYA PENDIDIKAN KEWIRAUSAHAAN DALAM MEMBENTUK KARAKTER SISWA - Sucipto, Sucipto (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Entrepreneurship education is a crucial aspect in shaping students' character from an early age, particularly in addressing the increasingly complex global challenges. This study explores the implementation and impact of entrepreneurship education at SMK Negeri 1 Jombang. The aim of this research is to identify the influence of this program on the development of students' entrepreneurial spirit, including self-confidence, creativity, and problem-solving skills. The methods used include participatory observation and in-depth interviews with students and teachers. The findings reveal that entrepreneurship education enhances students' critical thinking and initiative-taking abilities, as evidenced by their confidence in presenting business ideas and product innovations. The program also facilitates students in becoming more proactive, independent, and competitive in entrepreneurial activities. Furthermore, collaborations with local communities and entrepreneurs provide relevant practical insights. Based on these findings, it is recommended that other schools integrate entrepreneurship education as an integral part of their curriculum to foster innovative and work-ready young generations. This research also contributes significantly to the educational literature by offering practical and context-based approaches to support character development in students.